PEMBUATAN VIDEO IKLAN PRODUK BAWANG GORENG SULTAN DENGAN MENGGUNAKAN APLIKASI VIDEOSCRIBE, CAPCUT DAN WONDERSHARE FILMORA - Yogi Dwiki Darmawan (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
The development of computer technology into the world of multimedia has now been used as a medium/tool for making designs, audio-visual, animation, text and images. This multimedia can also be used as a marketing medium for a product/service. Advertising has a very important role for product/service providers, to promote products/services to the public. The quality of advertisements also greatly influences the public to be interested in the products/services being offered.” Onion Fried Sultan, one of them, offers a fried onion product with various tastes and quality at affordable prices. There are many types of product advertisements, for example banners, billboards, videos, and many more. One way is to use animated videos. There are many advantages of animated videos, one of which is that a creator can have more imagination and the results are more interesting and creative. So it can attract better attention for the public to see it. In making this animated video there are still many shortcomings, such as inadequate equipment, this animation was designed using the CapCut application, Wondershare Filmora and some of the assets needed.